A Comprehensive Functional Analysis in Patients after Atrial Switch Surgery - Hornung, Andreas; Vollmer, Daniela; Wiegand, Gesa; Apitz, Christian; Latus, Heiner; Hofbeck, Michael; Sieverding, Ludger (The Thoracic and Cardiovascular Surgeon, 2021)
Background Long-term course after atrial switch operation is determined by increasing right ventricular (RV) insufficiency. The aim of our study was to investigate subtle functional parameters by invasive measurements with conductance technique and noninvasive examinations with cardiac magnetic resonance imaging (CMR).Methods We used invasive (pressure–volume loops under baseline conditions and dobutamine) and noninvasive techniques (CMR with feature tracking [FT] method) to evaluate RV function. All patients had cardiopulmonary exercise testing (CPET).Results From 2011 to 2013, 16 patients aged 28.2 ± 7.3 (22–50) years after atrial switch surgery (87.5% Senning and 12.5% Mustard) were enrolled in this prospective study. All patients were in New York Heart Association (NYHA) class I to II and presented mean peak oxygen consumption of 30.1 ± 5.7 (22.7–45.5) mL/kg/min. CMR-derived end-diastolic volume was 110 ± 22 (78–156) mL/m2 and RV ejection fraction 41 ± 8% (25–52%). CMR-FT revealed lower global systolic longitudinal, radial, and circumferential strain for the systemic RV compared with the subpulmonary left ventricle. End-systolic elastance (Ees) was overall reduced (compared with data from the literature) and showed significant increase under dobutamine (0.80 ± 0.44 to 1.89 ± 0.72 mm Hg/mL, p ≤ 0.001), whereas end-diastolic elastance (Eed) was not significantly influenced (0.11 ± 0.70 to 0.13 ± 0.15 mm Hg/mL, p = 0.454). We found no relevant relationship between load-independent conductance indices and strain or CPET parameters. Conductance analysis revealed significant mechanical dyssynchrony, higher during diastole (mean 30 ± 4% baseline, 24 ± 6% dobutamine) than during systole (mean 17 ± 6% baseline, 19 ± 7% dobutamine).Conclusions Functional assessment of a deteriorating systemic RV remains demanding. Conductance indices as well as the CMR-derived strain parameters showed overall reduced values, but a significant relationship was not present (including CPET). Our conductance analysis revealed intraventricular and predominantly diastolic RV dyssynchrony.
Keywords: congenital heart disease; CHD; heart failure; imaging (all modalities); Conductance